Stability and change in affective experience across the adult life-span: Analyses with a national sample from Germany - Ute Kunzmann; David Richter; Stefan C. Schmukle (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Using cross-sectional and longitudinal data from a national sample spanning the adult lifespan, age differences in anger and sadness were explored. The cross-sectional and longitudinal findings consistently suggest that the frequency of anger increases during young adulthood, but then shows a steady decrease until old age. By contrast, the frequency of sadness remains stable over most of adulthood and begins to increase in old age. In addition, the effects of age on happiness were investigated; the cross-sectional evidence speaks for a steady decrease in happiness across age groups, but within-person decline in happiness was only evident in old age. Together the findings provide further evidence for multidirectional age differences in affective experience and suggest that the overall quality of affective experience may deteriorate in old age.
Keywords: 330; emotion; affect; sadness; anger; happiness; aging; adult life-span; longitudinal change